Prioritizing Patient Reported Outcome Measures (PROMs) to use in the clinical care of youth living with mental health concerns: a nominal group technique study - Kalpana Thapa Bajgain; Justino Mendoza; Farwa Naqvi; Fariba Aghajafari; Karen Tang; Jennifer Zwicker; Maria-Jose Santana (SpringerOpen, 2024)
Abstract Background In the past few decades, particularly in the mental health setting, there has been growing interest in using Patient Reported Outcome Measures (PROMs) to assess the efficacy of the treatments in healthcare systems. Despite recent initiatives for global harmonization, there remains a lack of consensus on which PROMs are best practice and appropriate. Engagement of the service users, such as patients and family members/caregivers, is vital at this stage to ensure the selected PROMs are feasible, relevant, and acceptable to them. This study aimed to prioritize PROMs by youth and family/caregiver based on feasibility, relevance, and overall importance to be used in the clinical care of youth living with anxiety and/or depression. Methods Ten validated and widely used PROMs were presented to the patients and family/caregivers. Nominal group techniques were employed to prioritize the PROMs based on feasibility, relevance, and overall importance. Results For patients and families/caregivers, the PROMs, Revised Child Anxiety and Depression Scale (RCAD 25), and The Young Person's Core (YP-CORE) were the highest priorities. Both felt that RCAD 25 was comprehensive, short, easy, and quick to complete, whereas regarding YP-CORE, patients and family/caregivers thought it was also short and relevant. Due to some specific concerns, the Strength and Difficulties Questionnaire and Child Health Questionnaire were the lowest prioritized by patients and family/caregivers. Conclusion It is of utmost importance that patient's and family/caregivers' voices or opinions are considered while selecting and implementing PROMs in mental health settings. Our study provides practical recommendations around measures best suited to achieve this.